PENGARUH SKEPTISME PROFESIONAL DAN INDEPENDENSI AUDITOR TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (FRAUD) DI BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN (BPKP) DI DAERAH ISTIMEWA YOGYAKARTA - Paulince Grace Sigiro; Tutut Dewi Astuti (Multiplier: Jurnal Magister Manajemen, 2018)
The research is a comparative kausal research that aims to find out: (1) A professional skepticism of the ability of auditor in detectin deception, (2) The independent influence of auditor for the auditors’ ability to detect fraud and (3) The influence of professional skeptics and the independent of auditors are simultan as to the ability in detecting deficiencies. The populasi and research are the auditors who work for the Badan Pengawasan Keuangan dan Pembangunan (BPKP) Daerah Istimewa Yogyakarta. In this research using a sample of s much as 35 auditors from 70 auditors, where this policy is the policy of the Badan Pengawasan Keuangan dan Pembangunan (BPKP) Daerah Istimewa Yogyakarta. The research uses the questionnaires in the account of its data. The test technique used is a validation test technique and reliability test. The classic assumptions test include multisquinty testing tests, tests of normality, and the heterochromatic test. The hypothesis used in this research is the doble regression analysis. The result of this investigation indicates that: (1) professional skepticism has a effect on the ability of auditors in detecting deception, (2) the independent auditors has no effect on the ability of an auditor in detecting cheating, and (3) professional skeptics and independent auditors have a simultaneous effect on the ability of auditors in detecting deficiencies.